Sonographic Criteria for Earlier Detection of Molar Pregnancies - Gupta N; Botros S; Demetrios M; Blankstein J (Journal of Gynecological Research and Obstetrics - Peertechz Publications, 2020)
Objective: To establish the sensitivity of ultrasonography as a diagnostic tool in the early identification of molar pregnancies and to develop a sonographic diagnostic criterion in earlier detection of molar pregnancies. Methods: A case series study was implemented for 69 patients who were found to have a diagnosis of molar pregnancy, confirmed histologically by the pathology department. This retrospective study investigated these patients at Mount Sinai Hospital between 2014-2016. Study groups were defined and compared by sonographic findings based on the presence of a gestational sac, yolk sac, fetal pole and appearance of the uterine cavity. Additionally, the presence of theca- luteal cysts, size of the ovaries, uterine size, and endometrial thickness were examined as well. Results: of the 69 patients diagnosed pathologically with molar pregnancies, 48 had received ultrasounds for initial evaluation upon presentation. 27 of these patients showed sonographic features suggestive of molar pregnancies; 24 displayed the multi-cystic mass change, with an incidence of 89%. The incidence of visualization of the additional findings in these 27 cases were: A Gestational Sac (GS) (74%), a fetal pole (41%), uterine enlargement (33%) and the snowstorm appearance (19%). The 21 cases that did not show any sonographic evidence of molar pregnancies were diagnosed as: 10 missed abortions (21%), 4 early pregnancies (8%), 4 blighted ovums (8%), 1 ectopic pregnancy (2%), 1 early congenital anomaly (2%) and 1 inevitable abortion (2%). The imaging findings were compared in all patients with the histological material from endometrial curettage and /or hysterectomy. Conclusion: The presence of cystic changes of the endometrium and increased placental heterogeneity allows us to successfully diagnose and treat molar pregnancies during the first trimester. This method allows for earlier diagnosis than the "gold standard" snowstorm appearance; which is best visualized during the second or third trimester.